PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PT. TIMAH (YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2020) - Izmi, Imaniar; Maharani, Yunita; Shinta Lestari, Deara (Jurnal Akuntansi Bisnis Dan Keuangan, 2022)
This is an undergraduate thesis that had been developed by Imaniar Izmi, student identification number 130180047, tittled in Indoneisan : “Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan PT. Timah (Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2020)”. The purpose of this study is to analyze the effect of Good Corporate Governance consisting of Institutional Ownership, Board of Commissioners, Board of Independent Commissioners, Board of Directors, Audit Committee on Company Performance. The data used in this study is secondary data in the form of the company’s annual financial statements of PT. Tin is listed on the Indonesia Stock Exchange (IDX) in 2011-2020. The analytical method used is descriptive analysis method and multiple linear regression analysis with a quantitative approach to find the effect between the independent variable (Good Corporate Governance) and the dependent variable (Company Performance). The hypotheses in this study were tested and analyzed with the help of the JASP 0.14.1 Universileit-Van-Amsterdam program The results of the study show that institutional ownership has a partial or partial effect on the company’s performance, while the Board of Commissioners, the Board of Independent Commissioners, the Board of Directors, and the Audit Committee have no partial or simultaneous influence.